Reflection of Western Armenian Views on War and Peace, National Solidarity in the Periodical "Hayastan" - Karapetyan, Armen (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Весной 1914 г. по инициативе Зоравара Андраника в Тифлисе стала издаваться ежедневная газета «Айастан», редактором и сотрудниками которого были исключительно западные армяне. На страницах этого издания подробно обсуждались вопросы, связанные с дальнейшей судьбой переживших геноцид западных армян с восстановлением разрушенной Западной Армении и обороной фронта. Газета обращалась также к вопросу национальной солидарности между западными и восточными армянами, проблемам тысяч детей-сирот и мигрантов. Газета публиковала обращения-призывы многих известных представителей армянской и зарубежной интелегенции к армянам, пытаясь тем самым вселить в них уверенность в будущем. In the spring of 1914, on the initiative of Zoravar Andranik, “Hayastan” was published in Tiflis, the editor and staff of which were exclusively Western Armenians. On the pages of this journal, issues related to the future fate of thоse Western Armenians who had survived the genocide, the restoration of the destroyed country, and the front defense were discussed in detail. The journal regularly raised questions concerning the creation of an atmosphere of national solidarity between the Western Armenians and the Eastern Armenians, constantly addressing the problems and concerns of thousands of orphans and migrants. “Armenia” used to publish on its pages appeals and messages of well-known representatives of the Armenian and foreign intelligentsia, addressed to the Armenians who had gone through the unbelievable, thereby trying to internally warm the souls and cheer up the inner peace of mind of a scattered and suffering people, to give strength and confidence for the future.
Keywords: History